2000
DOI: 10.1016/s0022-5347(05)67441-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective Nonoperative Management of Blunt Grade 5 Renal Injury

Abstract: Conservative management of blunt grade 5 renal injury is feasible in patients who are hemodynamically stable at presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
70
0
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(87 citation statements)
references
References 12 publications
4
70
0
11
Order By: Relevance
“…1). Improvements in resuscitation management of trauma patients changed the concept of NOM in high-grade renal injury and highly-selective embolization skills shifted the treatment strategy toward NOM in severe blunt renal trauma patients [10][11][12]. Angioembolization was performed in cases of extravasation on abdominal/pelvic CT or of sus- In both the operative and NOM groups, no mortality was related to renal injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Improvements in resuscitation management of trauma patients changed the concept of NOM in high-grade renal injury and highly-selective embolization skills shifted the treatment strategy toward NOM in severe blunt renal trauma patients [10][11][12]. Angioembolization was performed in cases of extravasation on abdominal/pelvic CT or of sus- In both the operative and NOM groups, no mortality was related to renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Altman et al reported that patients managed conservatively had less morbidity [10]. Brewer et al successfully managed unstable grade V patients by percutaneous embolization [4].…”
Section: Discussionmentioning
confidence: 99%
“…23 Além da presença de hematúria macroscópica, devemos prestar atenção em traumas cujo mecanismo sugere impacto com grande desaceleração, tais como certos tipos de colisões automobilísticas e quedas de altura. 24 A TC suplantou a urografia excretora como o exame de imagem de escolha para a avaliação de pacientes politraumatizados com suspeita de trauma renal na maioria dos grandes centros de trauma. 24 Numerosos estudos mostraram as limitações da urografia excretora para estadiamento das lesões renais e comprovaram a superioridade da TC na definição dos detalhes anatômicos, mensuração do tamanho do hematoma perirenal e da profundidade da laceração renal, presença de extravasamento uriná-rio, integridade dos vasos renais e a presença e extensão das lesões extra-renais.…”
Section: -Trauma Renalunclassified
“…24 A TC suplantou a urografia excretora como o exame de imagem de escolha para a avaliação de pacientes politraumatizados com suspeita de trauma renal na maioria dos grandes centros de trauma. 24 Numerosos estudos mostraram as limitações da urografia excretora para estadiamento das lesões renais e comprovaram a superioridade da TC na definição dos detalhes anatômicos, mensuração do tamanho do hematoma perirenal e da profundidade da laceração renal, presença de extravasamento uriná-rio, integridade dos vasos renais e a presença e extensão das lesões extra-renais. 24 A TC mostrou ser capaz de fazer uma adequada identificação das lesões do pedículo renal, sendo a arteriografia indicada apenas quando os resultados da tomografia não são conclusivos.…”
Section: -Trauma Renalunclassified
See 1 more Smart Citation